2014
DOI: 10.1590/0004-2730000003043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and late effects on offspring metabolism

Abstract: Objective: The aim of this study was to evaluate the late effects of maternal obesity induced by lesion of the ventromedial hypothalamus on offspring metabolism. Materials and methods: Thirty days after the bilateral lesion of the ventromedial hypothalamus, female rats were mated and divided into 2 groups of pregnant animals: Control (C) -false lesion (sham) and Obese (OB) -lesion. Three months after that, with the groups of mothers, offspring were divided into control and obese animals that received a normoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…Findings were similar according to maternal treatment, except Western-type maternal diet tended to induce weaker effects on offspring when control diets were matched for energy (White et al, 2009) or micronutrient (Zhang et al, 2013) content. In general, offspring experimental diets were applied at weaning through the end of the study period; based on the small number exceptions (Arentson-Lantz et al, 2014; Brenseke et al, 2015; Couvreur et al, 2011; Khanal et al, 2014; Llopis et al, 2014; Ong and Muhlhausler, 2014; Vido et al, 2014; Wallace et al, 2012), we observed no remarkable patterns with regard to the post-gestational timing of exposure to experimental offspring diets.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Findings were similar according to maternal treatment, except Western-type maternal diet tended to induce weaker effects on offspring when control diets were matched for energy (White et al, 2009) or micronutrient (Zhang et al, 2013) content. In general, offspring experimental diets were applied at weaning through the end of the study period; based on the small number exceptions (Arentson-Lantz et al, 2014; Brenseke et al, 2015; Couvreur et al, 2011; Khanal et al, 2014; Llopis et al, 2014; Ong and Muhlhausler, 2014; Vido et al, 2014; Wallace et al, 2012), we observed no remarkable patterns with regard to the post-gestational timing of exposure to experimental offspring diets.…”
Section: Introductionmentioning
confidence: 78%
“…Of 39 studies reviewed, 35 were rodent studies, with others using pig (Arentson-Lantz et al, 2014), sheep (Khanal et al, 2014; Wallace et al, 2012), or non-human primate (Fan et al, 2013; Thorn et al, 2014) animal models. In all but two studies (Li et al, 2013; Vido et al, 2014), maternal obesity was induced by Western-type maternal diets. Findings were similar according to maternal treatment, except Western-type maternal diet tended to induce weaker effects on offspring when control diets were matched for energy (White et al, 2009) or micronutrient (Zhang et al, 2013) content.…”
Section: Introductionmentioning
confidence: 99%
“…Shankar et al [16] suggested that maternal obesity can be responsible for a fetal programming, resulting in late obesity. We have previously reported that maternal obesity altered the response of adult rats to the effects of hypercaloric diets [17].…”
Section: Introductionmentioning
confidence: 98%
“…It is increasingly clear that maternal obesity and high-fat (HF) diet during pregnancy and lactation can lead to adverse outcomes in the offspring (Bringhenti et al, 2013;Desai et al, 2014;Stachowiak et al, 2013;Vido et al, 2014;Zhang et al, 2011), as the intrauterine and early postnatal environments are critical to their development (Desai et al, 2014;Vogt et al, 2014). Maternal nutritional status during pregnancy and lactation plays an important role in determining the risk of developing metabolic diseases in adulthood, including type 2 diabetes, cardiovascular disease (CVD), hypertension, and obesity (Bouret, 2009;Heerwagen, Miller, Barbour, & Friedman, 2010;MacPherson et al, 2015;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%